A CROSS-SECTIONAL STUDY ON MOBILE TELEHEALTH SYSTEMS AND INFORMATION ACCESSIBILITY AT KITAGATA HOSPITAL IN SHEEMA DISTRICT. - Musiime Selwano, Jackson (Student's Journal of Health Research Africa, 2025)
Background Mobile telehealth systems are increasingly transforming healthcare delivery, improving accessibility for patients, and enhancing efficiency among healthcare providers. This study explored the current landscape of mobile telehealth system usage at Kitagata Hospital in Sheema district southwestern Uganda. Methods The cross-sectional research design was adopted. The study population included patients and Physicians in Kitagata Hospital while a sample size of 250 participated in the study. Questionnaires and in-depth interviews were used to collect data. The study employed both primary and secondary data. Descriptive statistics and regression technique (model summary) analysis were done to examine the percentage effect of mobile telehealth systems on information accessibility at Kitagata Hospital to analyze quantitative data while qualitative data was narratively analyzed. To cater for conflict of interest, familiarized with the institutions’ policies to minimize the chances of occurrence of conflict of interest, a research assistant was recruited to assist in data collection where the researcher had a conflict of interest. Results The combined total of 63.6% suggests that telehealth is becoming a routine part of healthcare delivery in this setting. Overall, results demonstrated that mobile telehealth systems significantly correlate with enhanced information accessibility at Kitagata Hospital, explaining a notable portion of the variability in this area. Also, a moderate level of adoption, with significant benefits reported in patient satisfaction and physician time management. Conclusion Whereas evidence shows that the use of telehealth systems increases efficiency and quality of healthcare, inadequate infrastructure development and insufficient capacity building among health workers inhibit the adoption and usage of telehealth. Recommendation More investment should be made in setting up appropriate infrastructure and building the capacity of healthcare workers to boost telehealth utilization.